Self Development Needs of Civil Service Personnels at the Central Prison, Bang Kwang, Mueng District, Nonthaburi Province - ช่วยเมือง, วิรัตน์; เล็กเลอสินธุ์, เสาวนารถ (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
This thesis objectives were to: 1) study self development needs of civil service personnels at Bang Kwang Mueng District, Nonthaburi Province, the central Prison and, 2) classify self development needs of Civil Service Personnels at the Central Prison, Bang Kwang, Mueng District, Nonthaburi Province based on personal status, population group, which consisted of totally 243 government officials, civil service employees, and hired staffs at the Central Prison at Bang Kwang Nonthaburi Province. The research tool was a questionaire . The statistics for data analysis was frequency, mean scores, and S.D. T-test and F-test were used for significance test. One Way ANNOVA and Pair test conducted with Scheffé Test at .05 significant Difference. The research results found that: 1) the holistic level of the civil service personnel’s self development at the Central Prison, Mueng District, Nonthaburi Province was high. And the mean scores of each category, and every category was at high levels and, 2) the group of samples with different sexes, age levels, status, and different employment condition had no different significance on self development needs except the ones with different education background. Those had self development needs higher and different on adult learning. And the experienced ones with different experiences with different needs had statistically significant difference on human relationship skill at .05.